Biological Activity of Complexes of Some Amino Acid: Review - Lekaa K. Abdul Karem, Israa M. Radhi, Suhad S. Mohammed (Indian Journal of Forensic Medicine & Toxicology, 2020)
Schiff bases (SBs) based on amino acid derivative stand for multipurpose ligands that formed by condensingamino acids with carbonyl groups. They are significant in pharmaceutical and medical areas due to theirwidespread biological actions such as antiseptic, antifungal, along with antitumor actions. Transitionmetallic complexes resulting from SB ligands with biological activity were extensively experimented in theliterature. In this article, we review, in details, about synthesizing and biological performances of SBs alongwith its complexes.